GAMBARAN PENGELOLAAN OBAT DI INSTALASI FARMASI RSUD PROVINSI SULAWESI BARAT - Tawazzun, A.Atirah Bunga; Aztriana, Aztriana; Nurlina, Nurlina (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
The management of pharmaceutical preparations, medical devices, and consumable medical materials is a cycle of activities, starting from selection, needs planning, procurement, receipt, storage, distribution, destruction and withdrawal, monitoring, and administration. This research aims to find out what management is like at Prof. Hospital. Dr. H. Anwar Makkatutu, Bantaeng Regency, and its compliance with the regulations in force in Indonesia. This research is descriptive and qualitative using guided interview methods as well as o, observation, review. The results showed that: the management was not fully in accordance with the Regulation of the Minister of Health Number 72 of 2016 concerning pharmaceutical service standards in hospitals while the management aspects that were not yet in accordance were accepted with a percentage of 77.77%, storage with a percentage of 93.54%, distribution with a percentage 85.71%, and destruction and withdrawal with a percentage of 85.71%.